Characterisation of plasma-sprayed fish scale hydroxyapatite/yttria stabilized zirconia bioceramic on titanium alloys for medical implants - Anene, Franklin Amaechi (2022)
Hydroxyapatite (HA) coating on metallic implants have been extensively used in orthopaedic applications to improve on the tissue-implant interactions, enhance their biocompatibility and functionality without altering the implant’s substrate properties. However, currently the expensive synthetic HA is widely used for coating of implants leading to the high cost of implants. Hence, the present research has explored the potentials of an inexpensive and halal natural biogenic HA derived from fish scales (FsHA) and FsHA doped with yttria stabilised zirconia (YSZ) bioceramic as an alternative coating material on Ti-6Al-4V and Ti- 13Nb-13Zr titanium alloys. In this research, the effect of post coating heat treatment at 750 oC on plasma sprayed FsHA and FsHA/YSZ coating materials were investigated. Spray dry technique was used to produce the fine FsHA powders while plasma spray technique was applied in the coating process on the surface of Ti alloys substrates. The FsHA and FsHA/YSZ powders used as feedstock for the plasma spray coating were examined by x-ray diffraction (XRD) technique, fourier transform infra-red (FTIR) and scanning electron microscopy/energy dispersive x-ray (SEM/EDX). Meanwhile the physicomechanical and bioactivity tests were conducted on the coated substrates to study their mechanical properties, corrosion resistance, wettability, in vitro bioactivity in simulated body fluid (SBF) and in vitro cytotoxicity. The results of the research showed that the crystallinity of the FsHA/YSZ powders was above 96%, the least crystallinity of the plasma sprayed coatings was 65.7% while the crystallinity of the heat-treated FsHA coatings was about 85%. From SEM analysis, the microstructure of the plasma sprayed coatings revealed fine lamellar with partially melted and unmelted FsHA particles as well as fine micro cracks along with evenly dispersed ZrO2 particles within the coating matrix of the FsHA/YSZ coatings. Post-coating treatment led to much denser and finer lamellar morphology with more cracks. It was observed that plasma sprayed FsHA coatings on both alloys produced rougher surfaces (4.316 and 4.215 μm) than heat treated coatings (3.881 and 3.916 μm). Plasma sprayed FsHA/20 wt.% YSZ coatings on both Ti alloys recorded the highest hardness values (558.5 and 536.9 Hv) compared to their undoped coatings (459 and 467.8 Hv). Further improvement in hardness strength for heat treated coated Ti alloys gave the maximum hardness values (631 and 651.6 Hv), respectively for doped coatings of FsHA/20 wt.% YSZ on both substrates. Similarly, YSZ doping of FsHA improved the adhesion strengths, wettability and coefficient of friction (CoF) of doped coatings. Additionally, the corrosion resistance of both alloys was significantly improved up to 80% (9.48 and 9.97 mmpy) with the deposition of FsHA/YSZ bioceramic coatings compared to their uncoated substrates (169.37 and 128.0 mmpy). Bioactivity evaluation of the plasma sprayed and post coating heat treatment indicated all the surfaces of the coatings were covered with well grown apatite layers after 21 days immersion in SBF solution. Besides, the in vitro cytotoxicity test of the coating demonstrated good cell viability (more than 95%) which indicated the FsHA/YSZ coated Ti alloys were proven to be biocompatible. Therefore, it can be concluded that the coating materials produced from this research work are suitable for biomedical applications.